Faktor yang Berpengaruh terhadap Ketegangan Otot Pekerja Pande Besi - Sari, Ernita; Chairudina, Erin; Suryono, Hadi; Marlik, Marlik (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2023)
Blacksmithing is a job that requires a lot of energy. Unnatural working positions can increase worker stress and may affect the risk of musculoskeletal disorders. Complaints of muscle strain occur in the part of the skeletal muscle that the worker feels, because the muscle is constantly under static load for a long time. This study aimed to identify the factors that influence muscle tone in blacksmith workers. The nature of this study was to use a cross-sectional approach to analytical observations. The total number of workers is 39, which are taken on a pro-rata basis. Data is collected through observations, interviews, and measurements. Physical workload was measured based on a person's heart rate, while work posture was assessed using RULA. The assessment of musculoskeletal disorders is based on the NBM approach. The data were then analyzed using chi-square and Fisher's exact test. The results showed that 41 percent of workers in the high group experienced muscle strains and 59 percent in the low group. The factors that affect the muscle tension of blacksmith workers are age, gender, working hours and working posture. Recommendations for industry are: managing rest periods, designing comfortable workplaces, providing sanitation facilities and educating about safe workplace.